Effects of perceived task complexity on the information types needed, information sources and channels used by lawyers - Adewale, Nafisat; Mansor, Yushiana (Institute of Electrical and Electronics Engineers Inc., 2014)
Tasks and its features, especially the complexity dimension has been identified as a major drive for information seeking. This study explores the effects of the perceived task complexity and uncertainty on the information types needed and the information sources used by commercial lawyers in Nigeria. A survey method was adopted and data was gathered with the use of questionnaires. The analysis and hypotheses testing was done using the smartPLS 2.0 M3 software. Findings indicate direct positive relationships among the constructs, except for the relationship between perceived task complexity and the information sources consulted by lawyers.